Preparation method of Ni-Sn bimetallic alloy catalyst and application of Ni-Sn bimetallic alloy catalyst in furfural hydrogenation reaction
The Ni-Sn bimetallic alloy catalyst prepared by glycine assisted spontaneous combustion method solves the problems of high cost of existing precious metal catalysts and environmental pollution of Cu-Cr-based catalysts, and achieves a high-efficiency and low-cost furfural hydrogenation reaction, which significantly improves the yield of 2-methylfuran.
Patent Information
- Application Number
- CN202411720716.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The existing precious metal catalysts are costly, Cu-Cr-based catalysts have environmental pollution problems and poor activity, making it difficult to effectively prepare highly selective 2-methylfuran.
The Ni-Sn bimetallic alloy catalyst was prepared by glycine-assisted spontaneous combustion method. The catalyst improved the geometric and electronic characteristics of Ni and improved the stability and activity of the catalyst by introducing the oxyphilic metal Sn.
The conversion rate of furfural and 2-methylfuran are significantly improved. The conversion rate of furfural can reach up to 100% and the yield can reach up to 99.8%, while reducing production costs and avoiding environmental pollution.
Smart Images

Figure CN119549157A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of Ni-Sn alloy catalyst and furfural hydrogenation, and in particular to a preparation method of a Ni-Sn bimetallic alloy catalyst and application of the catalyst in furfural hydrogenation reaction. Background Art
[0002] With the excessive consumption of non-renewable resources such as coal and oil, converting renewable biomass resources into biofuels and high-value chemicals has become an effective way to solve the problem of resource scarcity. As an important part of biomass resources, the development and utilization of agricultural and forestry waste can not only effectively alleviate the energy crisis, but also help solve the problem of excess agricultural and forestry waste. As a major agricultural country, my country produces a large amount of agricultural and forestry waste every year, such as corn cobs, straw, bagasse, etc. These resources are mainly processed by direct incineration or abandonment and landfill, with low utilization rate, which not only causes waste of resources, but also pollutes the environment. Therefore, agricultural and forestry waste must be further transformed.
[0003] Furfural can be produced directly from biomass resources such as corn cobs. It is one of the most important lignocellulose-derived biomass platform compounds. It has the characteristics of wide sources and low cost. It is considered to be a bridge connecting biomass raw materials and industrial production. It is widely used in medicine, pesticides and biofuels. Furfural can be used to prepare a series of high value-added chemicals such as furfuryl alcohol, tetrahydrofurfuryl alcohol, 2-methylfuran, cyclopentanone, pentanediol, etc. through catalytic hydrogenation. Among them, 2-methylfuran is an important chemical and pharmaceutical intermediate, widely used in the fields of fragrances, medicines and pesticides. In addition, 2-methylfuran has the remarkable characteristics of high octane number, fast combustion speed and excellent anti-knock performance, so it is widely used as a high-performance gasoline additive.
[0004] The production of 2-methylfuran is mainly prepared by furfural hydrogenation and deoxygenation. In industry, Cu-Cr catalysts are mainly used for the production of 2-methylfuran, which can obtain a 2-methylfuran yield of about 70%. Although Cu-Cr catalysts show certain activity and selectivity, the serious environmental pollution caused by chromium, a toxic metal, cannot be ignored at a time when environmental protection awareness is increasing. Therefore, it is of great research value to develop a new green and efficient catalyst for the hydrogenation of furfural to prepare 2-methylfuran.
[0005] At present, a large number of studies have shown that precious metal catalysts (Pt, Pd, Ru, etc.) show extremely high activity in the reaction of furfural hydrodeoxygenation to prepare 2-methylfuran, but the selectivity of 2-methylfuran is low due to the difficulty in suppressing side reactions. Panagiotopoulou et al. used Ru / C catalyst for furfural hydrogenation to prepare 2-methylfuran. After reacting for 5 hours at 180°C, the yield of 2-methylfuran can reach 61% (P. Panagiotopoulou, DG Vlachos, Liquid phase catalytic transfer hydrogenation of furfural over a Ru / C catalyst, Applied Catalysis A: General. 480 (2014) 17-24.). In addition, the expensive price of precious metals has also greatly hindered its practical application. Therefore, it is urgent to develop a low-cost and efficient catalyst for furfural hydrodeoxygenation to prepare 2-methylfuran.
[0006] Xiao Linfei et al. (CN110054602A) of Heilongjiang University invented a cobalt phosphide catalyst and applied it to the reaction of furfural hydrogenation to prepare 2-methylfuran. The catalyst was 2 After 4 hours of reaction under the conditions of , the conversion rate of furfural can reach 100%, and the selectivity of 2-methylfuran can reach more than 89%, but the higher reaction temperature places higher requirements on the reaction equipment.
[0007] Wang Kangjun et al. from Shenyang University of Chemical Technology (CN109529835A) invented a CuO-M / SiO 2 The preparation method of the catalyst (M is Zr, Mg, etc.) is as follows. First, a soluble metal Cu salt and a soluble auxiliary salt are mixed and dissolved in water, and after the solution is stirred evenly, silica sol or silicate is added, and then ammonium carbonate or urea is added and sealed and stirred, and then hydrothermal treatment is performed, and finally ultrasonic heating is performed to evaporate, and the precipitation is further washed, dried and roasted to obtain CuO-M / SiO 2 Catalyst. In the CuO-M / SiO 2 A 100% furfural conversion rate and more than 95% 2-methylfuran selectivity were achieved on the catalyst, but the process of this method is relatively complicated.
[0008] Nickel-based catalysts are widely used in various fields due to their high cost-effectiveness and significant hydrogenation activity. However, the strong interaction between metal Ni and the furan ring further leads to the occurrence of furan ring hydrogenation, which will increase the selectivity of tetrahydrofurfuryl alcohol and reduce the yield of 2-methylfuran. Therefore, it is very necessary to inhibit the hydrogenation of the furan ring. The introduction of oxophilic metals such as Ga, Sn, and Fe into Ni-based catalysts to form alloys or intermetallic compounds can effectively change the geometric and electronic properties of Ni, which can not only inhibit the adsorption and hydrogenolysis of CC bonds, but also enhance the adsorption of CO / C=O by the catalyst and promote the activation of CO / C=O bonds. Among them, tin is a cost-effective and easily available element that can achieve selective hydrogenation of C=O bonds while maintaining the integrity of the furan ring. Summary of the invention
[0009] In view of the technical problems that the above-mentioned precious metal catalysts are too high in cost, the catalytic effect of Cu-Cr series catalysts is poor and they may cause environmental pollution, the present invention provides a method for preparing a Ni-Sn bimetallic alloy catalyst and its application in a furfural hydrogenation reaction. Low-cost nickel nitrate and tin chloride are used as raw materials, and a glycine-assisted spontaneous combustion method is adopted to prepare an oxophilic metal Sn-doped Ni-Sn bimetallic catalyst. The catalyst does not require the use of Cr, is low in cost, is environmentally friendly, can reduce the production cost, improve the stability of the catalyst, and achieve a good catalytic effect.
[0010] The technical solution adopted by the present invention is as follows:
[0011] A method for preparing a Ni-Sn bimetallic alloy catalyst comprises the following steps:
[0012] S1. Adding a soluble nickel salt, a soluble tin salt and an amino acid to deionized water, stirring well and then ultrasonically treating to obtain a solution A;
[0013] S2. Add ammonium molybdate to deionized water, stir well, and then ultrasonicate to obtain solution B;
[0014] S3. Add solution A obtained in S1 dropwise into solution B obtained in S2, and then stir to obtain a mixed solution C;
[0015] S4. After stirring, the mixed solution C obtained in S3 was placed in an oil bath to evaporate water until a gel was obtained;
[0016] S5. The gel obtained in S4 is dried, and then the dried solid is ground into a powder;
[0017] S6. The powder obtained in S5 is placed in a crucible, the crucible is heated to 300-350°C in a muffle furnace, and then the heating rate is reduced to 650-700°C, maintained for 4-8h, and then naturally cooled to obtain a catalyst precursor;
[0018] S7. The catalyst precursor obtained in S6 is placed in a tubular furnace, heated to 350°C to 550°C in a hydrogen atmosphere, and reduced for 2 to 6 hours to obtain a Ni-Sn bimetallic alloy catalyst.
[0019] Furthermore, in S1, the soluble nickel salt is nickel nitrate, nickel acetate, nickel carbonate, nickel chloride, etc.; the soluble tin salt is tin chloride, tin fluoride, tin bromide, etc.; the amino acid is glycine, glutamic acid, alanine, etc.; the molar ratio of the soluble nickel salt, the soluble tin salt and the amino acid is 1-0.5:0.01-0.5:9-10.
[0020] Furthermore, in S2, the molar ratio of ammonium molybdate to soluble metal salt is 1:1 to 1.1, more preferably 1:1; and the soluble metal salt is the sum of soluble nickel salt and soluble tin salt.
[0021] Furthermore, in S1 and S2, the ultrasonic treatment time is 15 to 50 min, more preferably 25 to 35 min.
[0022] Furthermore, in S3, the stirring time is 8 to 16 hours, more preferably 12 to 14 hours.
[0023] Furthermore, in S4, the temperature of the oil bath is 60 to 100°C, more preferably 70 to 80°C.
[0024] Furthermore, in S5, the drying temperature is 80 to 120° C., more preferably 100 to 110° C.; the drying time is 12 to 36 hours, more preferably 24 to 28 hours.
[0025] Furthermore, in S6, the heating rate to 300-350°C is 4-6°C·min -1 , more preferably 5℃·min -1 ; The heating rate to 650-700°C is 1-2°C·min -1 , more preferably 1℃·min -1 .
[0026] The application of the Ni-Sn bimetallic alloy catalyst obtained by the above preparation method in the furfural hydrogenation reaction comprises the following steps: the reaction is carried out in a high-pressure reactor, furfural, a reaction solvent and the above-mentioned Ni-Sn bimetallic alloy catalyst with a mass percentage of 5 to 20% of furfural are added into the reactor, hydrogen is introduced to control the pressure to be 1 to 3 MPa, the reaction temperature is 140 to 190°C, and the reaction time is 6 to 10 h (more preferably the reaction temperature is 170°C, the reaction pressure is 2 MPa, and the reaction time is 8 h).
[0027] Furthermore, the reaction solvent is preferably isopropanol, methanol, ethanol, etc.; the ratio of the reaction solvent to furfural is 80 to 100:1, more preferably 100:1.
[0028] The beneficial effects of the present invention are:
[0029] The present invention uses low-cost nickel nitrate and tin chloride as raw materials, and adopts a glycine-assisted spontaneous combustion method to prepare a Ni-Sn bimetallic catalyst doped with an oxophilic metal Sn. The introduction of the oxophilic metal Sn not only promotes the adsorption and activation of the catalyst to furfural, which is beneficial to improving the selectivity of 2-methylfuran, but also the strong interaction between Ni and Sn promotes the formation of Ni-Sn alloy, greatly improving the ability and catalytic activity of the catalyst to dissociate hydrogen. The catalyst obtained by the present invention can reduce the requirements for reaction equipment and production costs, while also avoiding environmental pollution problems and improving the stability of the catalyst, significantly improving the conversion rate of furfural and the yield of 2-methylfuran, the conversion rate of furfural can reach up to 100%, and the yield can reach up to 99.8%, achieving a good catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the X-ray diffraction pattern of the Ni-Sn bimetallic alloy catalyst obtained in Example 1.
[0031] Figure 2 This is a scanning electron microscope image of the Ni-Sn bimetallic alloy catalyst obtained in Example 1.
[0032] Figure 3 This is a transmission electron microscope image of the Ni-Sn bimetallic alloy catalyst obtained in Example 1. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0034] Example 1
[0035] (1) 0.233 g of nickel nitrate, 0.045 g of tin chloride and 0.751 g of glycine were placed in 40 mL of deionized water, stirred thoroughly and ultrasonically treated for 30 min to obtain solution A;
[0036] (2) 1.236 g of ammonium molybdate tetrahydrate was placed in 50 mL of deionized water and ultrasonically treated for 30 min to obtain solution B;
[0037] (3) slowly dripping the solution A obtained in step (1) into the solution B obtained in step (2), and then continuing to stir at room temperature for 12 hours to obtain a mixed solution C;
[0038] (4) After stirring, the mixed solution C obtained in step (3) is placed in an 80° C. oil bath to slowly evaporate water until a gel is obtained;
[0039] (5) placing the gel obtained in step (4) in an oven at 100° C. and drying for 24 h, and then grinding the dried solid into powder;
[0040] (6) The powder obtained in step (5) is placed in a crucible and the crucible is heated in a muffle furnace at 5°C / min. -1 The temperature was raised to 300°C at a rate of 1°C·min -1 The temperature was raised to 700°C at a rate of , and maintained for 6 hours, and then naturally cooled to obtain a catalyst precursor;
[0041] (7) placing the catalyst precursor obtained in step (6) into a tubular furnace, heating it to 450° C. under a hydrogen atmosphere, and reducing it for 3 h to obtain a Ni—Sn bimetallic alloy catalyst;
[0042] (8) In a high-pressure reactor with a 50 mL liner, 0.15 g of furfural and 15 mL of isopropanol were added, and then 0.03 g of the Ni-Sn bimetallic alloy catalyst obtained in step (7) was added;
[0043] (9) After the reactor is sealed, the reactor body is leak-tested, and then the air in the reactor is evacuated with a vacuum pump to a vacuum state, and hydrogen is introduced to start heating;
[0044] (10) When the temperature of the reactor reaches 170°C, open the main valve and the air inlet valve of the hydrogen cylinder, adjust the pressure to 2 MPa, and record the reaction start time;
[0045] (11) After 8 hours, the reaction is over, the main valve of the hydrogen cylinder is closed, and the reactor is allowed to cool to room temperature naturally;
[0046] (12) Taking out the reaction solution, filtering and quantifying it; and using gas chromatography to perform quantitative and qualitative analysis on the product.
[0047] The reaction solution was analyzed by gas chromatography. The results showed that the conversion rate of furfural was 100% and the selectivity of 2-methylfuran was 99.81%.
[0048] The X-ray diffraction pattern of the Ni-Sn bimetallic alloy catalyst in Example 1 is as follows: Figure 1 The scanning electron microscope images are shown in Figure 2 As shown in the transmission electron microscope picture Figure 3 shown.
[0049] Example 2
[0050] (1) 0.242 g of nickel nitrate, 0.038 g of tin chloride and 0.751 g of glycine were placed in 40 mL of deionized water, stirred thoroughly and ultrasonically treated for 30 min to obtain solution A;
[0051] (2) 1.236 g of ammonium molybdate tetrahydrate was placed in 50 mL of deionized water and ultrasonically treated for 30 min to obtain solution B;
[0052] (3) slowly dripping the solution A obtained in step (1) into the solution B obtained in step (2), and then continuing to stir at room temperature for 12 hours to obtain a mixed solution C;
[0053] (4) After stirring, the mixed solution C obtained in step (3) is placed in an 80° C. oil bath to slowly evaporate water until a gel is obtained;
[0054] (5) placing the gel obtained in step (4) in an oven at 100° C. and drying for 24 h, and then grinding the dried solid into powder;
[0055] (6) The powder obtained in step (5) is placed in a crucible and the crucible is heated in a muffle furnace at 5°C / min. -1 The temperature was raised to 300°C at a rate of 1°C·min -1 The temperature was raised to 700°C at a rate of , and maintained for 6 hours, and then naturally cooled to obtain a catalyst precursor;
[0056] (7) placing the catalyst precursor obtained in step (6) into a tubular furnace, heating it to 450° C. under a hydrogen atmosphere, and reducing it for 3 h to obtain a Ni—Sn bimetallic alloy catalyst;
[0057] (8) In a high-pressure reactor with a 50 mL liner, 0.15 g of furfural and 15 mL of isopropanol were added, and then 0.03 g of the Ni-Sn bimetallic alloy catalyst obtained in step (7) was added;
[0058] (9) After the reactor is sealed, the reactor body is leak-tested, and then the air in the reactor is evacuated with a vacuum pump to a vacuum state, and hydrogen is introduced to start heating;
[0059] (10) When the temperature of the reactor reaches 170°C, open the main valve and the air inlet valve of the hydrogen cylinder, adjust the pressure to 2 MPa, and record the reaction start time;
[0060] (11) After 8 hours, the reaction is over, the main valve of the hydrogen cylinder is closed, and the reactor is allowed to cool to room temperature naturally;
[0061] (12) Taking out the reaction solution, filtering and quantifying it; and using gas chromatography to perform quantitative and qualitative analysis on the product.
[0062] The reaction solution was analyzed by gas chromatography, and the analysis results showed that the conversion rate of furfural was 100% and the selectivity of 2-methylfuran was 93.91%.
[0063] Example 3
[0064] (1) 0.218 g of nickel nitrate, 0.056 g of tin chloride and 0.751 g of glycine were placed in 40 mL of deionized water, stirred thoroughly and ultrasonically treated for 30 min to obtain solution A;
[0065] (2) 1.236 g of ammonium molybdate tetrahydrate was placed in 50 mL of deionized water and ultrasonically treated for 30 min to obtain solution B;
[0066] (3) slowly dripping the solution A obtained in step (1) into the solution B obtained in step (2), and then continuing to stir at room temperature for 12 hours to obtain a mixed solution C;
[0067] (4) After stirring, the mixed solution C obtained in step (3) is placed in an 80° C. oil bath to slowly evaporate water until a gel is obtained;
[0068] (5) placing the gel obtained in step (4) in an oven at 100° C. and drying for 24 h, and then grinding the dried solid into powder;
[0069] (6) The powder obtained in step (5) is placed in a crucible and the crucible is heated in a muffle furnace at 5°C / min. -1 The temperature was raised to 300°C at a rate of 1°C·min -1 The temperature was raised to 700°C at a rate of , and maintained for 6 hours, and then naturally cooled to obtain a catalyst precursor;
[0070] (7) placing the catalyst precursor obtained in step (6) into a tubular furnace, heating it to 450° C. under a hydrogen atmosphere, and reducing it for 3 h to obtain a Ni—Sn bimetallic alloy catalyst;
[0071] (8) In a high-pressure reactor with a 50 mL liner, 0.15 g of furfural and 15 mL of isopropanol were added, and then 0.03 g of the Ni-Sn bimetallic alloy catalyst obtained in step (7) was added;
[0072] (9) After the reactor is sealed, the reactor body is leak-tested, and then the air in the reactor is evacuated with a vacuum pump to a vacuum state, and hydrogen is introduced to start heating;
[0073] (10) When the temperature of the reactor reaches 170°C, open the main valve and the air inlet valve of the hydrogen cylinder, adjust the pressure to 2 MPa, and record the reaction start time;
[0074] (11) After 8 hours, the reaction is over, the main valve of the hydrogen cylinder is closed, and the reactor is allowed to cool to room temperature naturally;
[0075] (12) Taking out the reaction solution, filtering and quantifying it; and using gas chromatography to perform quantitative and qualitative analysis on the product.
[0076] The reaction solution was analyzed by gas chromatography, and the analysis results showed that the conversion rate of furfural was 97% and the selectivity of 2-methylfuran was 90.89%.
[0077] Example 4
[0078] (1) 0.194 g of nickel nitrate, 0.075 g of tin chloride and 0.751 g of glycine were placed in 40 mL of deionized water, stirred thoroughly and ultrasonically treated for 30 min to obtain solution A;
[0079] (2) 1.236 g of ammonium molybdate tetrahydrate was placed in 50 mL of deionized water and ultrasonically treated for 30 min to obtain solution B;
[0080] (3) slowly dripping the solution A obtained in step (1) into the solution B obtained in step (2), and then continuing to stir at room temperature for 12 hours to obtain a mixed solution C;
[0081] (4) After stirring, the mixed solution C obtained in step (3) is placed in an 80° C. oil bath to slowly evaporate water until a gel is obtained;
[0082] (5) placing the gel obtained in step (4) in an oven at 100° C. and drying for 24 h, and then grinding the dried solid into powder;
[0083] (6) The powder obtained in step (5) is placed in a crucible and the crucible is heated in a muffle furnace at 5°C / min. -1 The temperature was raised to 300°C at a rate of 1°C·min -1 The temperature was raised to 700°C at a rate of , and maintained for 6 hours, and then naturally cooled to obtain a catalyst precursor;
[0084] (7) placing the catalyst precursor obtained in step (6) into a tubular furnace, heating it to 450° C. under a hydrogen atmosphere, and reducing it for 3 h to obtain a Ni—Sn bimetallic alloy catalyst;
[0085] (8) In a high-pressure reactor with a 50 mL liner, 0.15 g of furfural and 15 mL of isopropanol were added, and then 0.03 g of the Ni-Sn bimetallic alloy catalyst obtained in step (7) was added;
[0086] (9) After the reactor is sealed, the reactor body is leak-tested, and then the air in the reactor is evacuated with a vacuum pump to a vacuum state, and hydrogen is introduced to start heating;
[0087] (10) When the temperature of the reactor reaches 170°C, open the main valve and the air inlet valve of the hydrogen cylinder, adjust the pressure to 2 MPa, and record the reaction start time;
[0088] (11) After 8 hours, the reaction is over, the main valve of the hydrogen cylinder is closed, and the reactor is allowed to cool to room temperature naturally;
[0089] (12) Taking out the reaction solution, filtering and quantifying it; and using gas chromatography to perform quantitative and qualitative analysis on the product.
[0090] The reaction solution was analyzed by gas chromatography, and the analysis results showed that the conversion rate of furfural was 95.28% and the selectivity of 2-methylfuran was 89.58%.
[0091] Example 5
[0092] (1) 0.145 g of nickel nitrate, 0.113 g of tin chloride and 0.751 g of glycine were placed in 40 mL of deionized water, stirred thoroughly and ultrasonically treated for 30 min to obtain solution A;
[0093] (2) 1.236 g of ammonium molybdate tetrahydrate was placed in 50 mL of deionized water and ultrasonically treated for 30 min to obtain solution B;
[0094] (3) slowly dripping the solution A obtained in step (1) into the solution B obtained in step (2), and then continuing to stir at room temperature for 12 hours to obtain a mixed solution C;
[0095] (4) After stirring, the mixed solution C obtained in step (3) is placed in an 80° C. oil bath to slowly evaporate water until a gel is obtained;
[0096] (5) placing the gel obtained in step (4) in an oven at 100° C. and drying for 24 h, and then grinding the dried solid into powder;
[0097] (6) The powder obtained in step (5) is placed in a crucible and the crucible is heated in a muffle furnace at 5°C / min. -1 The temperature was raised to 300°C at a rate of 1°C·min -1 The temperature was raised to 700°C at a rate of , and maintained for 6 hours, and then naturally cooled to obtain a catalyst precursor;
[0098] (7) placing the catalyst precursor obtained in step (6) into a tubular furnace, heating it to 450° C. under a hydrogen atmosphere, and reducing it for 3 h to obtain a Ni—Sn bimetallic alloy catalyst;
[0099] (8) In a high-pressure reactor with a 50 mL liner, 0.15 g of furfural and 15 mL of isopropanol were added, and then 0.03 g of the Ni-Sn bimetallic alloy catalyst obtained in step (7) was added;
[0100] (9) After the reactor is sealed, the reactor body is leak-tested, and then the air in the reactor is evacuated with a vacuum pump to a vacuum state, and hydrogen is introduced to start heating;
[0101] (10) When the temperature of the reactor reaches 170°C, open the main valve and the air inlet valve of the hydrogen cylinder, adjust the pressure to 2 MPa, and record the reaction start time;
[0102] (11) After 8 hours, the reaction is over, the main valve of the hydrogen cylinder is closed, and the reactor is allowed to cool to room temperature naturally;
[0103] (12) Taking out the reaction solution, filtering and quantifying it; and using gas chromatography to perform quantitative and qualitative analysis on the product.
[0104] The reaction solution was analyzed by gas chromatography, and the analysis results showed that the conversion rate of furfural was 91.75% and the selectivity of 2-methylfuran was 85.86%.
[0105] Comparative Example 1
[0106] (1) 0.233 g of nickel nitrate and 0.751 g of glycine were placed in 40 mL of deionized water, stirred thoroughly, and then ultrasonically treated for 30 min to obtain solution A;
[0107] (2) 1.236 g of ammonium molybdate tetrahydrate was placed in 50 mL of deionized water and ultrasonically treated for 30 min to obtain solution B;
[0108] (3) slowly dripping the solution A obtained in step (1) into the solution B obtained in step (2), and then continuing to stir at room temperature for 12 hours to obtain a mixed solution C;
[0109] (4) After stirring, the mixed solution C obtained in step (3) is placed in an 80° C. oil bath to slowly evaporate water until a gel is obtained;
[0110] (5) placing the gel obtained in step (4) in an oven at 100° C. and drying for 24 h, and then grinding the dried solid into powder;
[0111] (6) The powder obtained in step (5) is placed in a crucible and the crucible is heated in a muffle furnace at 5°C / min. -1 The temperature was raised to 300°C at a rate of 1°C·min -1 The temperature was raised to 700°C at a rate of , and maintained for 6 hours, and then naturally cooled to obtain a catalyst precursor;
[0112] (7) placing the catalyst precursor obtained in step (6) into a tubular furnace, heating it to 450° C. under a hydrogen atmosphere, and reducing it for 3 h to obtain a Ni-based monometallic catalyst;
[0113] (8) In a high-pressure reactor with a 50 mL liner, 0.15 g of furfural and 15 mL of isopropanol were added, and then 0.03 g of the Ni-based monometallic catalyst obtained in step (7) was added;
[0114] (9) After the reactor is sealed, the reactor body is leak-tested, and then the air in the reactor is evacuated with a vacuum pump to a vacuum state, and hydrogen is introduced to start heating;
[0115] (10) When the temperature of the reactor reaches 170°C, open the main valve and the air inlet valve of the hydrogen cylinder, adjust the pressure to 2 MPa, and record the reaction start time;
[0116] (11) After 8 hours, the reaction is over, the main valve of the hydrogen cylinder is closed, and the reactor is allowed to cool to room temperature naturally;
[0117] (12) Taking out the reaction solution, filtering and quantifying it; and using gas chromatography to perform quantitative and qualitative analysis on the product.
[0118] The reaction solution was analyzed by gas chromatography, and the results showed that the conversion rate of furfural was 79.71% and the selectivity of 2-methylfuran was 48.87%.
[0119] Comparative Example 2
[0120] (1) 0.045 g of tin chloride and 0.751 g of glycine were placed in 40 mL of deionized water, stirred thoroughly, and then ultrasonically treated for 30 min to obtain solution A;
[0121] (2) 1.236 g of ammonium molybdate tetrahydrate was placed in 50 mL of deionized water and ultrasonically treated for 30 min to obtain solution B;
[0122] (3) slowly dripping the solution A obtained in step (1) into the solution B obtained in step (2), and then continuing to stir at room temperature for 12 hours to obtain a mixed solution C;
[0123] (4) After stirring, the mixed solution C obtained in step (3) is placed in an 80° C. oil bath to slowly evaporate water until a gel is obtained;
[0124] (5) placing the gel obtained in step (4) in an oven at 100° C. and drying for 24 h, and then grinding the dried solid into powder;
[0125] (6) The powder obtained in step (5) is placed in a crucible and the crucible is heated in a muffle furnace at 5°C / min. -1 The temperature was raised to 300°C at a rate of 1°C·min -1 The temperature was raised to 700°C at a rate of , and maintained for 6 hours, and then naturally cooled to obtain a catalyst precursor;
[0126] (7) placing the catalyst precursor obtained in step (6) into a tubular furnace, heating it to 450° C. under a hydrogen atmosphere, and reducing it for 3 h to obtain a Sn-based monometallic catalyst;
[0127] (8) In a high-pressure reactor with a 50 mL liner, 0.15 g of furfural and 15 mL of isopropanol were added, and then 0.03 g of the Sn-based monometallic catalyst obtained in step (7) was added;
[0128] (9) After the reactor is sealed, the reactor body is leak-tested, and then the air in the reactor is evacuated with a vacuum pump to a vacuum state, and hydrogen is introduced to start heating;
[0129] (10) When the temperature of the reactor reaches 170°C, open the main valve and the air inlet valve of the hydrogen cylinder, adjust the pressure to 2 MPa, and record the reaction start time;
[0130] (11) After 8 hours, the reaction is over, the main valve of the hydrogen cylinder is closed, and the reactor is allowed to cool to room temperature naturally;
[0131] (12) Taking out the reaction solution, filtering and quantifying it; and using gas chromatography to perform quantitative and qualitative analysis on the product.
[0132] The reaction solution was analyzed by gas chromatography. The results showed that the conversion rate of furfural was 14.7% and the selectivity of 2-methylfuran was 19.6%.
[0133] Comparative Example 3
[0134] (1) 0.233 g of nickel nitrate and 0.045 g of tin chloride were placed in 40 mL of deionized water, stirred thoroughly, and then ultrasonically treated for 30 min to obtain solution A;
[0135] (2) 1.236 g of ammonium molybdate tetrahydrate was placed in 50 mL of deionized water and ultrasonically treated for 30 min to obtain solution B;
[0136] (3) slowly dripping the solution A obtained in step (1) into the solution B obtained in step (2), and then continuing to stir at room temperature for 12 hours to obtain a mixed solution C;
[0137] (4) After stirring, the mixed solution C obtained in step (3) is placed in an 80° C. oil bath to slowly evaporate water until a gel is obtained;
[0138] (5) placing the gel obtained in step (4) in an oven at 100° C. and drying for 24 h, and then grinding the dried solid into powder;
[0139] (6) The powder obtained in step (5) is placed in a crucible and the crucible is heated in a muffle furnace at 5°C / min. -1 The temperature was raised to 300°C at a rate of 1°C·min-1 The temperature was raised to 700°C at a rate of , and maintained for 6 hours, and then naturally cooled to obtain a catalyst precursor;
[0140] (7) placing the catalyst precursor obtained in step (6) into a tubular furnace, heating it to 450° C. under a hydrogen atmosphere, and reducing it for 3 h to obtain a Ni—Sn bimetallic alloy catalyst;
[0141] (8) In a high-pressure reactor with a 50 mL liner, 0.15 g of furfural and 15 mL of isopropanol were added, and then 0.03 g of the Ni-Sn bimetallic alloy catalyst obtained in step (7) was added;
[0142] (9) After the reactor is sealed, the reactor body is leak-tested, and then the air in the reactor is evacuated with a vacuum pump to a vacuum state, and hydrogen is introduced to start heating;
[0143] (10) When the temperature of the reactor reaches 170°C, open the main valve and the air inlet valve of the hydrogen cylinder, adjust the pressure to 2 MPa, and record the reaction start time;
[0144] (11) After 8 hours, the reaction is over, the main valve of the hydrogen cylinder is closed, and the reactor is allowed to cool to room temperature naturally;
[0145] (12) Taking out the reaction solution, filtering and quantifying it; and using gas chromatography to perform quantitative and qualitative analysis on the product.
[0146] The reaction solution was analyzed by gas chromatography. The results showed that the conversion rate of furfural was 80.3% and the selectivity of 2-methylfuran was 59.6%.
[0147] The above experimental results show that the Ni-Sn bimetallic catalyst prepared by the glycine-assisted spontaneous combustion method in the present invention significantly improves the conversion rate of furfural and the yield of 2-methylfuran. The conversion rate of furfural can reach up to 100%, and the yield can reach up to 99.8%, achieving a good catalytic effect; while when Ni-based monometallic catalysts, Sn-based monometallic catalysts or Ni-Sn bimetallic alloy catalysts prepared without the glycine-assisted spontaneous combustion method are used for furfural hydrogenation reaction, the conversion rate of furfural and the yield of 2-methylfuran are significantly reduced.
Claims
1. A method for preparing a Ni-Sn bimetallic alloy catalyst, characterized in that: The steps include: S1. Adding a soluble nickel salt, a soluble tin salt and an amino acid to deionized water, stirring well and then ultrasonically treating to obtain a solution A; S2. Add ammonium molybdate to deionized water, stir well, and then ultrasonicate to obtain solution B; S3. Add solution A obtained in S1 dropwise into solution B obtained in S2, and then stir to obtain a mixed solution C; S4. After stirring, the mixed solution C obtained in S3 was placed in an oil bath to evaporate water until a gel was obtained; S5. The gel obtained in S4 is dried, and then the dried solid is ground into a powder; S6. The powder obtained in S5 is placed in a crucible, the crucible is heated to 300-350°C in a muffle furnace, and then the heating rate is reduced to 650-700°C, maintained for 4-8h, and then naturally cooled to obtain a catalyst precursor; S7. The catalyst precursor obtained in S6 is placed in a tubular furnace, heated to 350°C to 550°C in a hydrogen atmosphere, and reduced for 2 to 6 hours to obtain a Ni-Sn bimetallic alloy catalyst.
2. The method for preparing the Ni-Sn bimetallic alloy catalyst according to claim 1, characterized in that: In S1, the soluble nickel salt is at least one of nickel nitrate, nickel acetate, nickel carbonate or nickel chloride; the soluble tin salt is at least one of tin chloride, tin fluoride or tin bromide; the amino acid is at least one of glycine, glutamic acid or alanine; the molar ratio of the soluble nickel salt, the soluble tin salt and the amino acid is 1-0.5:0.01-0.5:9-10.
3. The method for preparing the Ni-Sn bimetallic alloy catalyst according to claim 1, characterized in that: In S2, the molar ratio of ammonium molybdate to the soluble metal salt is 1:1-1.1, and the soluble metal salt is the sum of the soluble nickel salt and the soluble tin salt.
4. The method for preparing the Ni-Sn bimetallic alloy catalyst according to claim 1, characterized in that: In S1 and S2, the ultrasonic treatment time is 15 to 50 min.
5. The method for preparing the Ni-Sn bimetallic alloy catalyst according to claim 1, characterized in that: In S3, the stirring time is 8 to 16 hours.
6. The method for preparing the Ni-Sn bimetallic alloy catalyst according to claim 1, characterized in that: In S4, the temperature of the oil bath is 60 to 100°C.
7. The method for preparing the Ni-Sn bimetallic alloy catalyst according to claim 1, characterized in that: In S5, the drying temperature is 80 to 120° C. and the drying time is 12 to 36 hours.
8. The method for preparing the Ni-Sn bimetallic alloy catalyst according to claim 1, characterized in that: In S6, the heating rate to 300-350°C is 4-6°C·min -1 ; The heating rate to 650-700°C is 1-2°C·min -1 .
9. Use of the Ni-Sn bimetallic alloy catalyst obtained by the preparation method according to any one of claims 1 to 8 in the hydrogenation reaction of furfural, characterized in that: The method comprises the following steps: the reaction is carried out in a high-pressure reactor, furfural, a reaction solvent and a Ni-Sn bimetallic alloy catalyst which accounts for 5-20% of the mass of furfural are added into the reactor, hydrogen is introduced to control the pressure to be 1-3MPa, the reaction temperature is 140-190°C and the reaction time is 6-10h.
10. The use according to claim 9, characterized in that: The reaction solvent is at least one of isopropanol, methanol or ethanol; the usage ratio of the reaction solvent to furfural is 80-100:1.
Citation Information
Patent Citations
Preparation method of catalyst for converting furfural into 2-methylfuran
CN109529835A
Method for preparing 2-methylfuran through furfural hydrogenation
CN110054602A